Cryptococcal sacroiliitis. Issue 2 (February 1985) - Brand, C; Warren, R; Luxton, M; Barraclough, D
Abstract : Disseminated cryptococcal disease is known to occur in patients with altered immune status. We have reported an unusual case of cryptococcal disease manifested solely by sacroiliitis, which occurred in a patient on chronic steroid therapy for autoimmune haemolytic anaemia. This case stresses the importance of considering unusual organisms as a cause of sepsis in patients with altered immune status.